2016
DOI: 10.4103/2231-0762.183108
|View full text |Cite
|
Sign up to set email alerts
|

A novel Chotta Bheem–Chutki scale for dental anxiety determination in children

Abstract: Objective:A potential problem in patient management in pediatric dentistry is dental anxiety among children. It is of paramount importance for pediatric dentists to identify an anxious child and review potential management options specific to every child. The aim of this study is to validate a newly devised Chotta Bheem–Chutki (CBC) pictorial scale and to compare this with Venham's pictorial scale (VPS) and facial image scale (FIS) to measure dental anxiety in young children during their first dental visit.Mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 14 publications
1
7
0
Order By: Relevance
“…This difference can be attributed to lower mean anxiety score of VPT (1.51) as compared to AES (1.78) and FIS (1.93). Lower mean anxiety scores with respect to VPT obtained is similar to the findings of Buchanan and Niven [4], Shetty RM et al [10] and is in contrast to the study by Sadana et al [6].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…This difference can be attributed to lower mean anxiety score of VPT (1.51) as compared to AES (1.78) and FIS (1.93). Lower mean anxiety scores with respect to VPT obtained is similar to the findings of Buchanan and Niven [4], Shetty RM et al [10] and is in contrast to the study by Sadana et al [6].…”
Section: Discussionsupporting
confidence: 87%
“…Till date, the literature shows various methods of assessing dental anxiety, including indirect methods (physiologic measurements of pulse rate, blood pressure, and muscle tension) [5] or projective techniques (children's dental fear picture test) [6] that require skills in carrying out interviews, and administering and scoring tests. The latter exhibited questionable reliability and validity due to difficulties in the interpretation of stories and standardizing scores.…”
Section: Introductionmentioning
confidence: 99%
“…Needless to say, the choice of method inappropriate to the child subject’s age and level of development could affect the ability of the assessment tool to reflect the level of dental fear and anxiety accurately. Many studies have pointed out plainly that very young children could not reliably report aspects of their own dental fear due to a minimum cognitive ability required to understand questions and to respond meaningfully [ 43 ] and require assistance from parents or other adults in answering questions [ 44 ]. Another study indicated that assessment tools using abstract numeric scales pose another challenge to respondents younger than the age of nine who might fare better with pictorial scales [ 45 ].…”
Section: Selection Of Assessment Methodsmentioning
confidence: 99%
“…Dental anxiety is usually measured using a wide range of available psychometric self-assessment scales such as Corah’s Dental Anxiety Scale (CDAS), 14 Modified Dental Anxiety Scale (MDAS), 15 State-Trait Anxiety Scale (STAI), 16 General Geer Fear Scale, 17 Getz Dental Belief Survey, 18 Chotta Bheem-Chutki Scale 19 and Dental Fear Survey (DFS). 20 These scales range from 1 item to 20 items or even more.…”
Section: Introductionmentioning
confidence: 99%